Assessment system for mathematics - E - Lim, Ee Siong. (2013)
Singapore has always focused its educational system towards a knowledge-based economy so much so that its education is being recognized as world class. In order for students to consistently do well for their examinations, the most traditional and recommended ways by parents and educators are to practice. The most common way is to buy assessment books in the market which comes in hardcopy. Not only is it expensive and environmentally-unfriendly, the questions that come with the books are limited, values are fixed and questions being asked are repetitive or not flexible enough to change and suit the students. Therefore it is neither good enough for the assessor to assess the understanding level of the students or to enhance the knowledge of the students.